(untitled) (Journal of Architectural Design, 2025)
This article explores the role of artistic creativity in the architectural environment, emphasizing the significance of practitioner-educators in shaping architectural spaces. It examines the impact of creative methodologies on fostering students’ heuristic thinking and unlocking their potential in architectural design. The study highlights the importance of engaging students in collaborative work, collective project development, and participation in competitive environments. Additionally, it discusses how such activities contribute to the cultivation of professional interests, the enhancement of design skills, and the understanding of competition within the architectural field.